(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Modern requirements for the implementation of competitive activities involve the formation of certain functional structures that ensure a high level of performance and the conditions for demonstrating the specific skills of athlete-dancers. During competitive activities, indicators such as oxygen consumption, carbon dioxide release, and pulmonary ventilation change according to the requirements of the components of functional support for specific performance. Specifically: Rapid kinetics: T50 (VO2, CO2, VE): partners – 28.9±2.9; 28.9±2.9; 26.5±3.2 & partners – 29.3±4.3; 27.6±4.0; 28.0±4.3. Steady state (SF – semifinal): VO2 max, VE/CO2, La VO2 max (recovery period SF – F); partners: 52.8±2.1 ml·min⁻¹·kg⁻¹; 38.7±0.8 units; 9.9±0.8 mmol·l⁻¹ & partners: 47.9±2.1 ml·min⁻¹·kg⁻¹; 29.3±0.8 units; 8.9±0.3 mmol·l⁻¹. Sustainable function development under fatigue compensation (F – final): VO2 max F, VE/CO2, La max (recovery period F); partners: 53.8±2.8 ml·min⁻¹·kg⁻¹; 39.7±1.2 units; 13.4±1.2 mmol·l⁻¹ & partners: 49.0±2.3 ml·min⁻¹·kg⁻¹; 32.9±0.9 units; 11.8±0.4 mmol·l⁻¹. Structural differences in the functional support of specific performance were identified between male and female dancers. Male dancers exhibit a balanced type of aerobic and anaerobic energy supply. Female dancers’ functional capabilities are characterized by a predominant influence of anaerobic glycolysis and respiratory compensation of metabolic acidosis. Ways to improve the functional preparedness of athlete-dancers were outlined. The first involves enhancing strength preparedness as a structural component of functional capabilities. The second focuses on optimizing the parameters of physiological load and recovery responses. These factors are a promising direction of research in sports - sports dancing.